Description Of The Reflection Of Islam In The Kazakh Literature Of The Soviet Era - Жумaжaновa Ф. Т.; Көптілеуовa Д. Т. (Journal of Oriental Studies, 2018)
This article examines the description of the reflection of Islam in the Kazakh literature of the Soviet era in the works of S.Seifullin, I.Zhansugurov and B.Maylin.